Análise da composição asfáltica com Agregado Sinterizado de Argila Calcinada (ASAC) segundo modelo reológico viscoelástico linear de Huet-Sayegh - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The current Brazilian pavement design method works with three parameters: support index, climatic parameters and traffic. Allied to this, the floors are a complex system, that is, they comprise several layers, especially the asphalt concrete, which contains in its composition the bituminous binder, a material whose behavior in terms of deformation is dualistic: elastic and viscous. To describe this phenomenon, the stress-strain behavior prediction is used by analyzing the complex modulus test. For the present work, two asphalt compositions from the work of Geotechnical Group (GEOTEC/UFAM) were analyzed: Asphalt Concrete (CA), under four-point bending test, and SMA mixture, with respect to the uniaxial behavior of cylindrical specimens. The methodology used was the adjustment of curves based on the experimental data of Complex Modulus |E*| and frequency, relative to the Ordinary Least Squares (OLS), to find the parameters of the Huet-Sayegh Rheological Model. The numerical analysis demonstrated the applicability of the model for determining the linear viscoelastic behavior, in the adopted temperature and frequency ranges.
Keywords: Concreto asfáltico; Modelo Reológico de Huet-Sayegh; Comportamento viscoelástico linear; Comportamento uniaxial; Comportamento tensão-deformação; ENGENHARIAS; Método dos Mínimos Quadrados; Huet-Sayegh; Módulo Complexo; Mistura Asfáltica